A meta-analysis of normal and disordered personality across the life span.[article]. - Ferguson, Christopher J.
Debate continues about whether personality, both normal and disordered, can change significantly or is mainly stable across the life span. One issue that receives a little attention is the degree to which personality stability coefficients may be influenced by attenuation due to measurement error. The current mete-analysis examines the date from recent research on personality stability, reporting both uncorrected and corrected stability coefficients. Attenuation due to measurement error was found to cause a significant reduction in personality stability coefficients, raising the possibility that some studies may conflate personality change with measurement error. Overall, corrected stability coefficients suggested that the stability of personality across adulthood is high, with only modest change. By contrast, personality during childhood is significantly more changeable. Both normal personality and personality disorders were highly stable across the life span, and patients in therapy experienced no more personality change than did nonpatients. Cross-cultural comparisons suggested relatively similar levels of personality stability cross-culturally. although personality stability among people in south pacific nations is slightly slower than among those in the United States, Canada, or European nations.
Keywords: Personality traits; Personality development; Personality disorders; Life span; Personality change